Attempt at application of the International Classification of Functioning, Disability and Health (ICF) in the domains of body and structure function and activity and participation in the assessment of the rate of disability in patients with morbid obesity – pilot study - Sosada, Krystyn; Gluck, Marek; Mizgała, Elżbieta; Lukas, Witold; Oleksiak, Aleksandra; Paliga, Jakub; Borek, Irena; Drzastwa, Witold; Izydorczyk, Bernadetta; Matuszewska-Zbrońska, Hanna; Zbroński, Karol; Bujak-Rosenbeiger, Ewa (Family Medicine & Primary Care Review, 2017)
Background. Due to the constant increase in the number of morbidly obese patients, an adequate tool for assessing the functioning and disability of these patients is being sought. The International Classification of Functioning, Disability and Health (IC F) could be that tool. Objectives. The aim of this study is to examine the usefulness of the IC F scale in assessing the functioning of morbidly obese patients in two selected areas in reference to recognized scales. Material and methods . The study group included 76 patients with morbid obesity qualified for bariatric treatment. The ICF was applied to assess the function and limitations of each individual. Two domains of the IC F were selected: Body Functions and Structures and Activities and Participation. The usefulness of the IC F was compared to that of the Barthel and EPQ-R scales. Results . In morbidly obese patients, a correlation between motor functions and IC F and BMI, as well as age, was observed. A significant correlation was observed between BMI and psychomotor control, appropriateness and range of emotions experienced, age and amount of sleep, quality of sleep, memory retrieval and psychomotor functions. Women’s mental functions were significantly worse than those of men. In terms of interpersonal relations, a correlation between BMI and regulating behavior within interactions was observed. Conclusions . The IC F is a useful tool for the study and description of the functioning of patients with morbid obesity. The selected domains are described better than by the previously used Barthel scale. Women with morbid obesity tend to have more impaired mental functioning than morbidly obese men.